DNA Analysis of Juvenile Scalloped Hammerhead Sharks Sphyrna lewini (Griffith, 1834) Reveals Multiple Breeding Populations and Signs of Adaptive Divergence in the South Pacific - Marie, Amandine D.; Stockwell, Brian L.; Rico, Ciro (Frontiers in Marine Science, 2019)
Shark species have undergone drastic population declines in recent decades due to overfishing and habitat destruction; thus, establishing connectivity among the populations of various shark species is important to determine the appropriate units and spatial scale for conservation and management, particularly as this group is long-lived with late age of maturation. Consequently, we used DNA variation at 1,317 putatively neutral and 25 potentially adaptive single nucleotide polymorphisms (SNPs) to analyze population genetic structure among 174 unrelated individuals of scalloped hammerhead sharks (Sphyrna lewini) from the Rewa Delta and the Ba Estuary, where documented aggregations of neonates and young-of-the-year occur in the island of Viti Levu, Republic of Fiji. Results of the pairwise FST analysis for the neutral loci revealed a small but significant genetic differentiation (FST: 0.004; P-value = 0.0009). Furthermore, the 25 potentially adaptive loci (i.e. under putative selection) revealed a magnitude of differentiation four times bigger than the estimate obtained using neutral genetic diversity (FST: 0.017; P-value = 0.0009). Interestingly, population assignment tests, using the neutral SNP data set and two different software packages, Admixture and assignPOP, provided evidence for the existence of up to four genetically differentiated populations among our samples. Assignment probabilities ranged from 0.98 ± 0.01 to 0.81 ± 0.03. Admixture and assignPOP assigned the same individuals to the same putative populations for all sampled neonates. Thus, our results provide unequivocal evidence that adult females from multiple genetically differentiated breeding populations contribute to these juvenile aggregation sites.